2000
DOI: 10.1590/s1517-83822000000400011
|View full text |Cite
|
Sign up to set email alerts
|

Culture conditions for the production of thermostable amylase by Bacillus sp

Abstract: Studies on the α-amylase production were carried out with a bacterial strain isolated from a soil sample. The cells were cultivated in a mineral medium containing soluble starch as sole carbon source. The addition of calcium (10 mM) or peptone (1%) and yeast extract (0.5%) to the mineral medium shortened the lag period and improved the growth and α-amylase synthesis. The addition of glucose to the culture diminished greatly the synthesis of α-amylase, demonstrating that a classical glucose effect is operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 19 publications
7
44
1
1
Order By: Relevance
“…). This finding on lowering of enzyme yield under excess nitrogen supplementation is in agreement with earlier reported work (10,15,27,35). Corn starch was used at 30 g L -1 , other parameters are as indicated in Table 1.…”
Section: Resultssupporting
confidence: 92%
“…). This finding on lowering of enzyme yield under excess nitrogen supplementation is in agreement with earlier reported work (10,15,27,35). Corn starch was used at 30 g L -1 , other parameters are as indicated in Table 1.…”
Section: Resultssupporting
confidence: 92%
“…In the presence of glucose and fructose, amylase production was almost nil; and that was a proof that glucose and fructose repressed amylase synthesis by L. fermentum 04BBA19. This observation is in agreement with the reports of Theodoro and Martin [64] showing that synthesis of carbohydrate degrading enzymes in some microbial species leads to catabolic repression by substrate such as glucose and fructose. Similar results were observed by Halsetine et al [65] for the production of amylase by the hyperthemophilic archeon Sulfolobus solfataricus.…”
Section: Optimisation Of Amylase and Lactic Acid Productionsupporting
confidence: 93%
“…The crude α-amylase of the Citrobacter sp. has a comparable temperature activity range with that of Bacillus sp reported by Teodoro and Martins (2000) but was however less stable. The pH activity and stability profiles of the organism showed that at a pH range of 3 -6, there was no appreciable difference in amylase activity.…”
Section: Amylase Activity (U/ml)mentioning
confidence: 55%